Test loan loss provision hypothesis on commercial banks in UK - Wang, Lufei (2019)
In this paper, we investigated four hypothesizes of loan loss provision on commercial banks in UK based on a sample of 70 British commercial banks. During the process of analysis, we used three methodologies including Stochastic Frontier Analysis (SFA), OLS regression and Generalized Method of Moments (GMM). The results show that income smoothing hypothesis and procyclicality hypothesis are supported by UK commercial banks, while there is no evidence to support capital management hypothesis and bank efficiency hypothesis